ANALISIS POTENSI PAJAK PERTAMBAHAN NILAI (PPN) TERHADAP LAYANAN OVER THE TOP (OTT) LUAR NEGERI DI INDONESIA - Wayan Hesadijaya Utthavi; Luh Arik Chitta Wati; Ni Made Ayu Dwijayanti; Kadek Nita Sumiari (UNHI Press, 2023)
Digital evolution now affects almost all aspects of people’s lives. The emergence of products resulting from technological developments was responded to very positively by the community. One of them is digital-based entertainment, namely streaming services with a fairly high number of viewers. The positive direction of growth in digital entertainment consumption is trying to be linked to tax revenues, especially the type of VAT to see how much it contributes to the state. Digital entertainment that can be marketed around the world via a network called over the top initially poses a dilemma of collecting its contributions, so various strategies have been devised to solve this dilemma. Tracing the potential VAT revenue on digital entertainment consumption in Indonesia is the main object of this study. Research by the qualitative trying to probe deeper onto the ground of the VAT through the public interest in accessing digital entertainment. This study took advantage of the primary data of the views of experts in the field of taxation and supported secondary data. The results of this study indicate that the high interest of the public in using digital entertainment, which is indicated by the rapid growth of access to digital services in Indonesia, is a great potential for state revenues that can be collected through taxation. As a new source of income in the VAT type of tax sector, the use of digital entertainment in Indonesia can be optimized for VAT collection and deposit through the enactment of PMK No. 60/PMK.030/2022 and PER-12/PJ/2020. That has not been optimized in the field of supervision and the right to fulfill a sense of fairness for all taxpayers in Indonesia is a note and evaluation for authority taxation in their bid to the undertaking of duty calculated the contributions to digital providers foreign in Indonesia.